Implementation Of The Humanistic Approach In Forming Students’ Moral Character At Muhammadiyah 2 Middle School Medan - Ratih Naila Siregar; Azizah Hanum OK (IJGIE (International Journal of Graduate of Islamic Education), 2026)
Strengthening students’ moral character has become a strategic issue amidst the complexities of modern education, characterized by social change, the penetration of digital technology, and growing challenges regarding the internalization of values. A humanistic approach is considered relevant as it positions students as active subjects of learning who possess potential, needs, and the capacity for reflection. This study aims to analyze the implementation of a humanistic approach in shaping students’ moral character at SMP Muhammadiyah 2 Medan. A qualitative research method employing a case study approach was used. The participants consisted of two teachers and three students, selected purposively based on their involvement in the learning process. Data were gathered through observation, in-depth interviews, and documentation, then analyzed using an interactive process involving data reduction, data display, and conclusion drawing. The results indicate that the humanistic approach is implemented through dialogic learning, empathetic interaction, respect for learning experiences, and the creation of an environment that fosters moral reflection. Teachers act as facilitators, mentors, and role models in the internalization of values. Student responses include increased moral awareness, responsibility, discipline, social concern, and the ability to make ethical decisions. Successful implementation is reinforced by family support through the habitual practice of values ​​and communication aligned with the school; however, limited instructional time restricts the depth of moral reflection, while the heterogeneity of students’ characters, backgrounds, and abilities necessitates more adaptive teaching strategies. These findings demonstrate that a humanistic approach is effective in strengthening students’ moral character when supported by synergy among the school, teachers, and families.